REGION DU QUEBEC, TENDANCES ET ACCOMPLISSEMENTS EN SCIENCES DE L'INFORMATION/QUEBEC REGION, TRENDS & ACCOMPLISHMENTS IN INFORMATION SCIENCES - Lelievre, Philippe; Ste-Marie, Jean (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF